The Effect of Music on Store Shopping: Mediating Role of the Time Spent of Customer in Store - seyyed hamid khodadad (تحقیقات بازار یابی نوین, 2013)
Competition issue in today’s market is not exclusively limited to manufacturing enterprises. Suppliers and especially big retailers are increasingly facing this challenging problem too. Regarding to the context of Iranian culture, big retailers are against very large number of small groceries that their successfully survival depends on how they operate intelligently. These kinds of retailers in order to attract customers and increase their shopping volume need to utilize new marketing methods to increase the amount of time spent in store and consequently increase the probability of shopping. One of these methods is playing music in store. The purpose of this study is to investigate the effect of music on customer shopping through the time spent by customer in store. The present study is a survey research in terms of method and an applied-developmental research. Rashtianshoppersof Rasht Big Stores are selected as statistical population. Results using path analysis approach reveals that the effect of music on customer shopping through the time spent in store is confirmed. On the other hand, there are numerous differences among customers with various demographic characteristics.